Logic Test Educational Game for Children Based on Multimedia - Ndruru, Yufita Friska; Jamaluddin, Jamaluddin; Simamora, Roni Jhonson; Harianja, Eva Julia Gunawati (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2024)
Along with the development of information technology, the rapid use of technology as a learning media is very good to apply. Many ways can be done to improve the quality of education. This research was conducted by creating an interactive learning media product in the form of a logic test educational game where students are required to learn to solve existing logic problems. The multimedia-based logic test educational game for children is designed to develop children's logic, measure intelligence levels, and become an alternative means of fostering students' interest in learning. The research method used is the method of literature study, interviews, and observations, the stages of analysis and definition of needs, the stages of system and software design, the stages of implementation, and unit testing. The appearance of educational games is designed to be attractive, which is accompanied by images and quizzes that improve student memory and provide new experiences for students. The implementation of this educational game has been carried out on students of SD Negeri 060934 and the results show the enthusiasm level of the students towards the educational game used.